A corner of the universe - Martin, Ann M., 1955- (New York : Scholastic Inc., 2002)
The summer that Hattie turns twelve, she meets the childlike uncle she never knew and becomes friends with a girl who works at the carnival that comes to Hattie's small town.
Keywords: Family life -- Fiction; Uncles -- Fiction; People with mental disabilities -- Fiction; Friendship -- Fiction